Is nitrogen present in Li3N·P2S5 solid electrolytes produced by ball milling? - Hartley, G; Jin, L; Bergner, B; Spencer Jolly, D; Rees, G; Zekoll, S; Ning, Z; Pateman, A; Holc, C; Adamson, P; Bruce, P (American Chemical Society, 2019)
Nitrogenous solid electrolytes such as lithium phosphorus oxynitride (LiPON) have effectual interfacial compatibility with lithium metal; in part, this has enabled the development of thin-film solid-state batteries with excellent long-term cycling performance. However, most known nitrogen-containing solid electrolytes lack the ionic conductivity required for high-power/high-capacity batteries; therefore, the development of new nitrogenous solid electrolytes with increased ionic conductivity is highly desirable. The mechanical milling of lithium nitride (Li3N) with phosphorus pentasulfide (P2S5) has previously been reported to produce amorphous lithium-ion conductors, but the composition of these materials and the reactions occurring during the milling processes were hitherto undetermined. Here, we show that mechanochemically milled Li3N·P2S5 solid electrolytes contain less nitrogen than expected as N2 gas is released during an early stage of the ball milling process. Li3N·P2S5 solid electrolytes are mixtures composed of multiple lithium thiophosphates, lithium sulfide, and red phosphorus. We show that amorphous Li3PS4 is responsible for the ionic conductivity of Li3N·P2S5 electrolytes produced by ball milling.